In Vitro and In Vivo Evaluation of the Effect of Puerarin on Hepatic Cytochrome P450-Mediated Drug Metabolism - Kim, Sang-Bum; Yoon, In-Soo; Kim, Kyu-Sang; Cho, Sung-Jun; Kim, Yeong Shik; Cho, Hyun-Jong; Chung, Suk-Jae; Chong, Saeho; Kim, Dae-Duk (Planta Medica, 2014)
Puerarin (8-β-D-glucopyranosyl-7-hydroxy-3-(4-hydroxyphenyl)-4H-1-benzopyran-4-one) is a major pharmacological component of Puerariae Radix, the root of Pueraria lobata. We investigated the effect of puerarin on hepatic cytochrome P450-mediated drug metabolism in rats and humans. The in vitro cytochrome P450 inhibitory effect of puerarin in human and rat liver microsomes was evaluated using the following model cytochrome P450 substrates: phenacetin for CYP1A, diclofenac for CYP2C, dextromethorphan for CYP2D, and testosterone for CYP3A. The in vivo pharmacokinetics of intravenous and oral buspirone, a probe substrate for CYP3A, was studied with single simultaneous intravenous coadministration of puerarin in rats. In the in vitro cytochrome P450 inhibition study, the rate of disappearance of testosterone was significantly reduced in the presence of 10 µM PU, while that of other cytochrome P450 substrates was not significantly affected in both human and rat liver microsomes, suggesting that puerarin inhibits the in vitro hepatic CYP3A-mediated metabolism in the human and rat systems (IC50 = 15.5 ± 3.9 µM). After intravenous administration of buspirone with single simultaneous coadministration of intravenous puerarin at a dose of 10 mg/kg in rats, the total area under the plasma concentration–time curve from time zero to time infinity was increased while time-averaged total body clearance decreased. When buspirone was orally administered in rats with the 10 mg/kg intravenous puerarin coadministration, both total area under the plasma concentration–time curve from time zero to time infinity and the extent of absolute oral bioavailability were significantly increased. Therefore, results of the in vitro microsomal and in vivo pharmacokinetic studies suggest the possible inhibition of hepatic CYP3A-mediated drug metabolism by puerarin administration, potentially leading to metabolism-mediated herb–drug interactions with clinical significance.
Keywords: puerarin; Pueraria lobata; Fabaceae; cytochrome P450; buspirone; hepatic metabolism; pharmacokinetics